Multi-peak nonuniform model of rust distribution and corrosion-induced concrete cracking in reinforced concrete slabs - Bui, Huy Tang (2023)
Corrosion-induced concrete cracking is of importance in evaluating service life of reinforced concrete (RC) slabs. Rust distribution and steel bar configuration are two of the most parameters affecting not only internal and surface crack patterns, but also evolution of surface crack width. In this paper, a mathematical model based on Asymmetrical Generalised von Mises distribution (AGvM model) was proposed to simulate multi-peak asymmetrical nonuniform rust layer around the steel bar's circumference. Besides, an advanced 3D finite element (FE) model was developed incorporating rust distribution obtained from the AGvM model to simulate corrosion-induced concrete cracking. An experimental programme of six RC slabs with three different steel bar configurations and two corrosion levels was conducted to validate the AGvM and the FE models. As a result, it showed that the proposed AGvM model was capable of simulating rust distribution around the steel bar better than the other six existing mathematical models, especially when the rust layer had two peaks and its distribution was highly asymmetrical. Moreover, the 3D FE model could reasonably predict internal and surface crack patterns, as well as evolution of surface crack width of RC slabs. Based on the test results and numerical models, effects of steel bar configurations on corrosion-induced concrete cracking were discussed.